Progress of LMJ-relevant implosions experiments on OMEGA - Casner A.; Philippe F.; Tassin V.; Seytor P.; Monteil M.-C.; Gauthier P.; Park H.S.; Robey H.; Ross J.; Amendt P.; Girard F.; Villette B.; et al. (EPJ Web of Conferences, 2013)
In preparation of the first ignition attempts on the Laser Mégajoule (LMJ), an experimental program is being pursued on OMEGA to investigate LMJ-relevant hohlraums. First, radiation temperature levels close to 300 eV were recently achieved in reduced-scale hohlraums with modest backscatter losses. Regarding the baseline target design for fusion experiments on LMJ, an extensive experimental database has also been collected for scaled implosions experiments in both empty and gas-filled rugby-shaped hohlraums. We acquired a full picture of hohlraum energetics and implosion dynamics. Not only did the rugby hohlraums show significantly higher x-ray drive energy over the cylindrical hohlraums, but symmetry control by power balance was demonstrated, as well as high-performance D2 implosions enabling the use of a complete suite of neutrons diagnostics. Charged particle diagnostics provide complementary insights into the physics of these x-ray driven implosions. An overview of these results demonstrates our ability to control the key parameters driving the implosion, lending more confidence in extrapolations to ignition-scale targets.